The Importance of Implementing Culturally Responsive Teaching on ASEAN Countries - Sri Trisnawati; Karin Selma Al-Kautsar; Hidayatul Hamdiah; Sri Trisna Dewi (CV. Creative Tugu Pena, 2020)
A class with various need and kind of students has been widely issued among teachers especially in ASEAN countries. Several studies had been conducted to encounter the best solution to handle this issue. Therefore, this article was conducted as the effort to find the solution regarding this issue. This study focuses on Culturally Responsive Teaching in ASEAN countries through examining the previews studies regarding Culturally Responsive Teaching by using PRISMA protocol to collect articles that relevant to this study. The result found that based on 10 articles CRT has found two key points on this matter. Those are misconception of CRT and CRT as the bridge between teacher and student to overcome high-power distance. Keywords: Culturally Responsive Teaching, High-power distance, ASEAN